2019
DOI: 10.1016/j.ijsolstr.2019.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of self-consistent and crystal plasticity FE approaches for modelling the high-temperature deformation of 316H austenitic stainless steel

Abstract: The present article examines the predictive capabilities of a crystal plasticity model for inelastic deformation which captures the evolution of dislocation structure, precipitates and solute atom distributions at the microscale, recently developed by Hu and Cocks [1,2]. The model is implemented within a self-consistent framework and a crystal plasticity finite element (CPFE) scheme. Through direct comparison between the two CP schemes and with an extensive material database for Type 316H stainless steel, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 69 publications
(147 reference statements)
2
23
0
Order By: Relevance
“…The response of the individual anisotropic grains is modelled through crystal plasticity (CP) theory, which is treated within a small-deformation framework, since the SCM developed by Hu and Cocks [2] is built within a framework where lattice rotations are ignored. Petkov et al [47] have compared predictions using the SCM model with full 3-D large deformation CPFE simulations and demonstrated that for the range of problems of interest here (macroscopic strains up to 5%) the current small deformation assumption provides an accurate description of the macroscopic response. The plastic strain rate in each crystal can be determined via the CP model by summation of the slip rates on individual slip systems within the crystal.…”
Section: Crystal Plasticity Frameworkmentioning
confidence: 99%
“…The response of the individual anisotropic grains is modelled through crystal plasticity (CP) theory, which is treated within a small-deformation framework, since the SCM developed by Hu and Cocks [2] is built within a framework where lattice rotations are ignored. Petkov et al [47] have compared predictions using the SCM model with full 3-D large deformation CPFE simulations and demonstrated that for the range of problems of interest here (macroscopic strains up to 5%) the current small deformation assumption provides an accurate description of the macroscopic response. The plastic strain rate in each crystal can be determined via the CP model by summation of the slip rates on individual slip systems within the crystal.…”
Section: Crystal Plasticity Frameworkmentioning
confidence: 99%
“…The symmetry plane was fixed from translation in the normal direction, x 2 = 0, the nodes on the top surface were traction free, while the remaining four surfaces of the cube were fixed. Elastic anisotropy was used with the following elastic constants for copper: Further details on the UMAT can be found in [60,63,64,65,62,66]. Simulations provide direct comparison with the EF scratch test.…”
Section: Crystal Plasticity Finite Element Modellingmentioning
confidence: 99%
“…An integrated multi-scale model incorporating model grain geometries and orientations and crystal plasticity was recently demonstrated for creep in 316H stainless steel [51]. Applying this method to model gradient microstructures may shed light on the relation between grain size gradients and creep damage, see [52] for an example.…”
Section: Stress Distribution Simulationmentioning
confidence: 99%